Characterization of haze pollution in Zibo, China: Temporal series, secondary species formation, and PMx distribution. (January 2022) - Li, Hui; Ma, Yongliang; Duan, Fengkui; Huang, Tao; Kimoto, Takashi; Hu, Yunxing; Huo, Mingyu; Li, Shihong; Ge, Xiang; Gong, Wanru; He, Kebin
Abstract: An online field observation was conducted in Zibo, China from September 1, 2018 to February 28, 2019, covering autumn and winter. Within the investigation period, the mean mass concentrations of PM1, PM2.5, and PM10 were 49.3, 86.1, and 136.5 μg m −3, respectively. OA (organic aerosol) was the most dominant species in PM2.5 (39.7 %), followed by NO3 − (26.3 %) and SO4 2− (17.0 %), indicating the importance of secondary species on PM2.5 . Increase of particles were always accompanied increasing relative humidity (RH), slow wind, and increasing precursors, contributing the secondary transition. SO4 2− was more susceptible to RH, indicating the dominant role of heterogeneous processes in its secondary formation. As RH increased, its strengthening effect on SO4 2− increased as well. Photochemistry was the main contributor to the secondary formation of NO3 − . The morning and evening rush hours determined the peak of absolute NO3 − throughout the day. By classifying particles into three bins, we found that smaller particles were the biggest contributors (larger PM1 /PM2.5 ) of slight pollution (35 < PM2.5 <115 μg m −3 ). When severe haze occurred, PM2.5 contributed more than particles of other sizes (PM1 or PM10 ). Secondary species contributed more to particles within 2.5 μm but less to larger particles. PM1 /PM2.5 was high from 9:00 to 15:00, indicating the strong effect of photochemistry on smaller particles. In comparison, larger particles favored more humid conditions. NO3 − preferentially existed in larger particles because the hygroscopicity of preexisting species (SO4 2− and NO3 − ) promoted partitioning. SO4 2− appeared a stable diurnal variation, replying its stable contribution to particles of different sizes. Graphical abstract: Image 1 Highlights: OA accounted most in species (39.7 %), followed by NO3 − (26.3 %) and SO4 2− (17.0 %). SO4 2− formation was facilitated by higher RH whose strengthening effect increased as increasing RH. PM1 contributed more to slight pollution, while PM2.5 contributed to severe haze significantly. Secondary species contributed to particles within 2.5 μm but less to larger size.